2020
DOI: 10.3390/e22080826
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the Intra- and Inter-Lobe Connectivity of the Brain Structural Network in Normal Aging

Abstract: The morphological changes in cortical parcellated regions during aging and whether these atrophies may cause brain structural network intra- and inter-lobe connectivity alterations are subjects that have been minimally explored. In this study, a novel fractal dimension-based structural network was proposed to measure atrophy of 68 parcellated cortical regions. Alterations of structural network parameters, including intra- and inter-lobe connectivity, were detected in a middle-aged group (30–45 years old) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The propensity may be that the age‐associated decline of structural modular architecture of the human cortical brain is hemispherically asymmetric: middle‐aged individuals generally have higher co‐coordination of nodes within the left hemisphere and lower co‐coordination of nodes within the right hemisphere compared with young and elderly adults. Previous research has found significantly lateralized atrophy of the left hemisphere in the elderly, which may relevant to the downward trend of intramodular connectivity within the left hemisphere since middle‐age 39 . The higher co‐coordination within the right hemisphere since middle‐age seems to be the compensation for the connectivity decrease and functional loss 39 …”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The propensity may be that the age‐associated decline of structural modular architecture of the human cortical brain is hemispherically asymmetric: middle‐aged individuals generally have higher co‐coordination of nodes within the left hemisphere and lower co‐coordination of nodes within the right hemisphere compared with young and elderly adults. Previous research has found significantly lateralized atrophy of the left hemisphere in the elderly, which may relevant to the downward trend of intramodular connectivity within the left hemisphere since middle‐age 39 . The higher co‐coordination within the right hemisphere since middle‐age seems to be the compensation for the connectivity decrease and functional loss 39 …”
Section: Discussionmentioning
confidence: 92%
“…Previous research has found significantly lateralized atrophy of the left hemisphere in the elderly, which may relevant to the downward trend of intramodular connectivity within the left hemisphere since middle-age. 39 The higher co-coordination within the right hemisphere since middle-age seems to be the compensation for the connectivity decrease and functional loss. 39…”
Section: Age-associated Spatial Distribution Of Hubsmentioning
confidence: 99%
See 1 more Smart Citation
“…One may conceive that hemispheric asymmetry could result in uneven thermodynamics between the brain hemispheres [ 136 ] but the structural analysis of intra- and inter-lobe connectivity is beyond the present work.…”
Section: Spontaneous Processesmentioning
confidence: 99%
“…In this regard, the combination of measures from information theory with both structural and functional connectivity analyses yields a new framework to further understand brain organization. This can be observed in the work of Jao et al [ 10 ], in which irregularity of the network anatomical structure, in particular inter- and intra-lobe brain connectivity, was analyzed using the fractal dimension. Their results suggested that aging induces morphological changes in the structural brain network generated from magnetic resonance imaging (MRI), which could be related to rewiring and reconfiguring modules as compensatory mechanisms for the functional deficit in inter- and intra-lobe brain connectivity.…”
mentioning
confidence: 96%